Methods Of Teaching Programming at The University - Markhamat Y. Khaydarova (Zien Journals, 2024)
This article explores five effective methods for teaching programming at the university level, aiming to address the diverse needs of students and enhance their learning experience. The five methods discussed include interactive learning, project-based education, peer learning and collaboration, the use of tools and simulators, and flipped classroom techniques. Each method is analyzed in terms of its benefits and practical implementation in the classroom environment. Interactive learning emphasizes active student participation through coding exercises and immediate feedback. Project-based education focuses on real-world application by assigning students hands-on projects that develop both technical and soft skills
Keywords: Methods; interactive learning; project-based learning; Peer learning